Analytical Evaluation of the WebSocket and WebTransport Protocols for the Class of SCADA Systems Operating Within the Intranet - G. A. Zvonareva; A. S. Smirnov (Открытое образование (Москва))
The purpose of research. In recent years, web technologies have been actively used in many process control systems, including SCADA. Such systems allow continuous monitoring of the test object in real time. In this regard, there is a need for frequent data transmission for their further display. To solve this problem, network protocols are used, which continue to develop rapidly to this day.Materials and methods. SCADA systems are used in many industries: aviation, ground transportation, rocket and space technology, systems for receiving and processing telemetry information. Among them, a class of SCADA systems operating within the intranet stands out. This can be an internal network of the enterprise, a hangar or a small test stand for tracking the indexes of measuring equipment. Therefore, today, more than ever, open and publicly available materials are important for understanding modern network solutions that reduce the time spent on data transmission and their further visualization. Such information will be of particular value to students studying network and web technologies.Results. As a result of the research, taking into account the limitations of the SCADA system and network being developed, the time characteristics for the WebSocket and WebTransport protocols have been determined, and the most optimal solution for a typical load is proposed. In the presented paper, the issues of data transfer between the client and server parts for a class of SCADA systems operating within an intranet are considered. In this regard, it is proposed to consider the two most suitable solutions for this task. These are application layer network protocols of the OSI model: WebSocket and WebTransport. In addition, transport layer protocols (TCP and QUIC) are taken into account, since they can also affect time characteristics. Data transmission issues are considered in the context of the SCADA data display and monitoring system. The server part is developed using C#, and the client is developed using JavaScript. A number of experiments are carried out for boundary cases and typical loads, on the basis of which the dependence of data transmission time on their volume is determined.Conclusion. The approach given in the paper on collecting network traffic and analyzing time characteristics will also be useful as part of the educational process for teaching students in the courses “Computer Networks” and “Internet Technologies”.